2015
DOI: 10.1016/j.nmni.2015.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Serologic and molecular survey for hepatitis E virus in wild boar (Sus scrofa) in Central Italy

Abstract: The aim of this study was to further investigate the role of wild boar (Sus scrofa) as a reservoir for hepatitis E virus (HEV). Sixty-four blood and faecal samples collected from wild boar hunted in Central Italy in 2011–2012 were examined by indirect enzyme-linked immunosorbent assay and RT-PCR analysis. Positive RT-PCR samples were further examined by nucleotide sequence determination and subsequent phylogenetic analysis. Thirty-six sera (56.2%) were positive for HEV-specific antibodies, and six (9.4%) faeca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
47
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 32 publications
3
47
2
Order By: Relevance
“…The relatively high detected HEV seroprevalence rate (57.05%) in Lithuanian wild boar serum was similar to previously published data from Italy (Mazzei et al 2015a) that revealed seroprevalence of 56.2% in the wild boar population. A Polish study determined 44.4% of HEV antibodies in the serum of wild boar from 11 different Polish provinces (Larska et al 2015), while a Spanish study found an overall seroprevalence of 42.7% in wild boar population from South Central Spain, whereas IgG seroprevalence ranged from 0% to 63.3% depending on geographical region.…”
Section: Discussionsupporting
confidence: 90%
“…The relatively high detected HEV seroprevalence rate (57.05%) in Lithuanian wild boar serum was similar to previously published data from Italy (Mazzei et al 2015a) that revealed seroprevalence of 56.2% in the wild boar population. A Polish study determined 44.4% of HEV antibodies in the serum of wild boar from 11 different Polish provinces (Larska et al 2015), while a Spanish study found an overall seroprevalence of 42.7% in wild boar population from South Central Spain, whereas IgG seroprevalence ranged from 0% to 63.3% depending on geographical region.…”
Section: Discussionsupporting
confidence: 90%
“…The time of sampling or the use of a different test could be the reason for the discordant results obtained by us and by Larska et al (9). Several studies have investigated the presence of HEV in wild boars in Italy, Germany, the Netherlands, and France (3,12,17,19). In Europe overall, the seroprevalence varies between 12% in the Netherlands (17) and 61.6% in Slovenia (7), with Spanish seroprevalence at 47.2% (5).…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic analysis also revealed that the identified HEV strains in wild boars in Romania were genetically related to human HEV strains circulating in Europe. Some studies highlighted that HEV genotypes 3a, 3c, 3h and 3i detected in wild boars showed a high sequence identity to human HEV strains from autochthonous hepatitis E cases (Forgach et al., ; Mazzei et al., ; Rutjes et al., ; Schielke et al., ). Subtype 3a has been described in humans in England and Portugal.…”
Section: Discussionmentioning
confidence: 99%
“…First indications of HEV infections in wild boars were made in 1999, when 17% of free‐living pigs investigated in Australia were found positive for anti‐HEV antibodies (Chandler, Riddell, Li, Love, & Anderson, ) but the first detection of HEV in wild boar was reported in 2004, in Japan (Sonoda et al., ). Across Europe, genotype HEV‐3 has been previously detected in wild boars from France (Jori et al., ; Kaba, Davoust, Marie, & Colson, ; Lhomme et al., ), Germany (Chandler et al., ; Kaci, Nockler, & Johne, ; Schielke et al., ), Hungary (Forgach et al., ; Reuter, Fodor, Forgach, Katai, & Szucs, ), Italy (Caruso et al., ; Martelli et al., ; Martinelli et al., ; Mazzei et al., ), Netherlands (Rutjes et al., , ), Belgium (Thiry et al., ) Sweden (Widen et al., ), Portugal (Mesquita, Oliveira, Coelho, Vieira‐Pinto, & Nascimento, ), Estonia (Ivanova et al., ) and Spain (de Deus et al., ) with prevalence rates ranging from 2.5% to 25% (Martelli et al., ). Adlhoch et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation